2000
DOI: 10.1248/bpb.23.298
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ginsenoside Deglycosylated by Intestinal Bacteria and Its Transformation to Biologically Active Fatty Acid Esters.

Abstract: Ginsenosides are deglycosylated by intestinal bacteria to active forms after oral administration. The present study demonstrated the pharmacodynamics of 20-O-beta-D-glucopyranosyl-20(S)-protopanaxadiol (M1), an intestinal bacterial metabolite of ginsenosides, and the in vitro and in vivo antitumor activities of M1-metabolites in comparison with M1 using C57BL/6 mice and Wistar rats. M1 was selectively accumulated into the liver soon after its intravenous administration to mice, and mostly excreted as bile; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 0 publications
4
58
0
Order By: Relevance
“…Some papers reported that the metabolites of traditional Chinese materia medica, such as GA and PM-I, yield stronger pharmacological effect than the original compound, [27][28][29][30][31][32] and they were the ultimate active components in vivo. The metabolic mechanism of HIF is an important link for the pharmacological study of Chinese material medica.…”
Section: Resultsmentioning
confidence: 99%
“…Some papers reported that the metabolites of traditional Chinese materia medica, such as GA and PM-I, yield stronger pharmacological effect than the original compound, [27][28][29][30][31][32] and they were the ultimate active components in vivo. The metabolic mechanism of HIF is an important link for the pharmacological study of Chinese material medica.…”
Section: Resultsmentioning
confidence: 99%
“…Screening 31 species of human intestinal bacteria, all of which has the -glucosidase activity, was carried out, and Eubacterium sp. A-44 (17) and Provotella orise (18) appeared to be responsible for metabolizing ginsenoside Rb-1.…”
Section: Metabolism Of Ginseng Saponinsmentioning
confidence: 99%
“…Pharmaceutical studies have shown that orally ingested ginsenoside passes through the stomach and small intestine without decomposition, but the colonic bacteria cleave the oligosaccharide connected to the aglycone stepwise from the terminal sugar to afford the major metabolite, ginsenoside-M 1 [13][14]. Previous studies also showed that ginsenoside-M 1 was further esterified with fatty acids which could be sustained longer in the body; this result indicated that fatty acid ester of the M 1 might be the real anti-tumor active species in vivo [15].…”
Section: Introductionmentioning
confidence: 98%